2022
DOI: 10.1111/neup.12802
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome inhibitor ameliorates ischemic stroke by reprogramming the phenotype of microglia/macrophage in a murine model of distal middle cerebral artery occlusion

Abstract: Stroke is one of the leading causes of death and disability worldwide. NLRP3 inflammasome has an essential role in the neuropathology of stroke. Recent studies report that shifting the microglial M1 phenotype to the M2 phenotype protects against ischemic stroke. In the present study, the precise effects of Tranilast, a NLPR3 inflammasome inhibitor, on stroke were evaluated. We established a murine model of distal middle cerebral artery occlusion (dMCAO) and administered Tranilast to dMCAO‐induced stroke mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The second most cited review is a review by Xiong et al 33 published in 2016 that systematically describes the role of microglia/macrophages in neuroinflammation and neurogenesis after stroke, and that NLRP3 plays an important role in glial cell/macrophage polarization. Notably, NLRP3 regulation of glial cell/macrophage polarization in ischemic stroke has been extensively studied in the following years and has become a major hotspot in this field 43–46 . These extensive publications indicate that NLRP3 regulates microglia/macrophage polarization through the nf–κb pathway, specifically by promoting M1 macrophage polarization to exacerbate ischemia–reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second most cited review is a review by Xiong et al 33 published in 2016 that systematically describes the role of microglia/macrophages in neuroinflammation and neurogenesis after stroke, and that NLRP3 plays an important role in glial cell/macrophage polarization. Notably, NLRP3 regulation of glial cell/macrophage polarization in ischemic stroke has been extensively studied in the following years and has become a major hotspot in this field 43–46 . These extensive publications indicate that NLRP3 regulates microglia/macrophage polarization through the nf–κb pathway, specifically by promoting M1 macrophage polarization to exacerbate ischemia–reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…30 The second most cited review is a review by Xiong et al 33 published in 2016 that systematically describes the role of microglia/macrophages in neuroin- a major hotspot in this field. [43][44][45][46] These extensive publications in- named "#0 nlrp3 inflammasome-mediated neuronal death", "#1 acupuncture", "#2 -induced interleukin-1 secretion", "#3 absence", "#4 natural compound", "#5 adenosine-dependent activation", "#6 telmisartan", "#7 tissue injury", "#8 il-1 production", "#9 acute stroke", and "#10 emerging role". Cluster#0 mainly focuses on NLRP3 inflammasome-mediated neuronal death, indicating the potential role of NLRP3 in neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has shown that MiR-423-5p could decrease the polarization of microglia/macrophage cells of the M1 phenotype by inhibiting the mRNA expression of NLRP3 in a spinal cord injury animal model [ 56 ]. Another study also found that Tranilast, an NLRP3 inflammasome inhibitor, could promote the polarization of microglia/macrophage from M1 type to M2 type and ameliorate ischemic stroke by inhibiting the NLRP3/caspase-1 pathway in a murine model of distal middle cerebral artery occlusion [ 57 ]. The activation of the NLRP3 inflammasome triggers the transformation of procaspase-1 to caspase-1, as well as the production and secretion of mature IL-1 β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…The activation was labeled with "+," and the inhibition was labeled with "-." type to M2 type and ameliorate ischemic stroke by inhibiting the NLRP3/caspase-1 pathway in a murine model of distal middle cerebral artery occlusion [57]. The activation of the NLRP3 inflammasome triggers the transformation of procaspase-1 to caspase-1, as well as the production and secretion of mature IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%